PRAWO PIERWOKUPU A SĄDOWY PODZIAŁ MAJĄTKU WSPÓLNEGO MAŁŻONKÓW - Jędrejek, Grzegorz (Zeszyty Prawnicze, 2016)
RIGHT OF FIRST REFUSAL AND THE DIVISION OF JOINT MATRIMONIAL PROPERTY Summary The aim of this article is to answer the question whether a court ruling awarding a particular asset of the joint matrimonial property to one of the spouses automatically means the expiry of the right of first refusal. The author’s position is that neither the contractual nor the statutory right of first refusal is extinguished by a court ruling on the division of the spouses’ jointly held assets. A legal decision whereby a particular asset is awarded to one of the spouses does not mean the cessation of the right of first refusal. The court conducting the division of joint matrimonial assets does not rule on the spouse’ liabilities or debts. Hence spouses who share liabilities cannot apply to a court to have the right of first refusal revoked.